Analisis Pengembangan Website Menggunakan Metode Kano (Studi Kasus: BRSPDF Budi Perkasa Palembang) - Mutiara Jesica; Gusmelia Testiana; Sri Rahayu (UNIVERSITAS INDO GLOBAL MANDIRI)
ABSTRACTThis research was conducted with the aim to find out the categories of attributes on the website of the Social Rehabilitation Center of Persons with Physical Disabilities Budi Perkasa Palembang so that it can be known the steps to improve or add content for development on the website, to determine the level of satisfaction and the level of user disappointment with the website, and to know the priority of applying content for development on the website later using the Kano method. After conducting interviews, Customer Requirements were obtained in the form of Content Home Improvements, Content Profiles Improvement, Online Registration Content Additions, Photo Gallery Content Improvements and Guest Book Content Additions. The results of this study found that the priority of implementing the first content is the addition of Online Registration content in the Must-Be category (with a satisfaction level of 0.375 and a level of disappointment -0.50), followed by improvements to the content of the Home (with a satisfaction level of 0.625 and a level of disappointment -0.625 ) and improvements to the Photo Gallery content (with a satisfaction level of 0.50 and a level of disappointment of -0,625) in the One Dimensional category, and finally the Improvement of the Profile content (with a level of satisfaction of 0.50 and a level of disappointment of -0.375) and the addition of the Guest Book content (with a satisfaction level of 0.50 and a level of disappointment -0.125) which is in the Attractive category.Keywords : Content, Kano Method, Social Rehabilitation Center for Persons with, Physical Disabilities Budi Perkasa PalembangABSTRAKPenelitian ini dilakukan dengan tujuan untuk mengetahui kategori dari atribut atribut dalam website Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik Budi Perkasa Palembang sehingga dapat diketahui langkah-langkah perbaikan atau penambahan content untuk pengembangan pada website, untuk mengetahui tingkat kepuasan dan tingkat kekecewaan pengguna terhadap website, dan untuk mengetahui prioritas penerapan content untuk pengembangan pada website nantinya dengan menggunakan metode Kano. Setelah dilakukan wawancara didapatkan Customer Requirement berupa Perbaikan Content Home, Perbaikan Content Profil, Penambahan Content Pendaftaran Online, Perbaikan Content Galeri Foto dan Penambahan Content Buku Tamu. Hasil dari penelitian ini didapatkan prioritas penerapan content yang pertama adalah penambahan content Pendaftaran Online yang masuk dalam kategori Must-Be (dengan tingkat kepuasan 0,375 dan tingkat kekecewaan -0,50) disusul dengan perbaikan content Home (dengan tingkat kepuasan 0,625 dan tingkat kekecewaan -0,625) dan perbaikan content Galeri Foto (dengan tingkat kepuasan 0,50 dan tingkat kekecewaan -0,625) yang berada pada kategori One Dimensional, dan yang terakhir Perbaikan content Profil (dengan tingkat kepuasan 0,50 dan tingkat kekecewaan -0,375) dan penambahan content Buku Tamu (dengan tingkat kepuasan 0,50 dan tingkat kekecewaan -0,125) yang berada pada kategori Attractive..Kata kunci: Content, Metode Kano, Balai Rehabilitasi Sosial Penyandang, Disabilitas Fisik Budi Perkasa Palembang